2014
DOI: 10.1002/jso.23665
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interval between neoadjuvant chemoradiotherapy and surgery for rectal cancer on surgical and oncologic outcome

Abstract: A neoadjuvant-surgery interval >7 weeks is safe and is associated with a higher rate of pCR and R0 resection, and decreased local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 28 publications
2
28
1
Order By: Relevance
“…Both sphincter preservation (OR 1⋅00, 95 per cent c.i. 0⋅88 to 1⋅14; P = 0⋅95) and stoma formation (OR 1⋅06, 0⋅83 to 1⋅36; P = 0⋅63) rates were similar for the Tran et al 22 Tulchinsky et al 23 De Campos-Lobato et al 24 Wolthuis et al 25 Saglam et al 33 Jeong et al 43 You et al 44 Zeng et al 46 Sirohi et al 45 Mihmanlı et al 49 Akbar et al 26 Garrer et al 50 Tran et al 22 Stein et al 21 Tulchinsky et al 23 De Campos-Lobato et al 24 Wolthuis et al 25 Jeong et al 43 You et al 44 Zeng et al 46 Sirohi et al 45 Akbar et al 26 Garrer et al 50 11 longer versus shorter interval (Figs S8-S10, supporting information).…”
Section: Duration Of Surgery Sphincter Preservation and Covering Stomentioning
confidence: 81%
See 3 more Smart Citations
“…Both sphincter preservation (OR 1⋅00, 95 per cent c.i. 0⋅88 to 1⋅14; P = 0⋅95) and stoma formation (OR 1⋅06, 0⋅83 to 1⋅36; P = 0⋅63) rates were similar for the Tran et al 22 Tulchinsky et al 23 De Campos-Lobato et al 24 Wolthuis et al 25 Saglam et al 33 Jeong et al 43 You et al 44 Zeng et al 46 Sirohi et al 45 Mihmanlı et al 49 Akbar et al 26 Garrer et al 50 Tran et al 22 Stein et al 21 Tulchinsky et al 23 De Campos-Lobato et al 24 Wolthuis et al 25 Jeong et al 43 You et al 44 Zeng et al 46 Sirohi et al 45 Akbar et al 26 Garrer et al 50 11 longer versus shorter interval (Figs S8-S10, supporting information).…”
Section: Duration Of Surgery Sphincter Preservation and Covering Stomentioning
confidence: 81%
“…). A total of 26 publications, including four RCTs and 25 445 patients with rectal cancer were eligible for inclusion ( Table ). Twenty‐four of the 26 studies (22 650 patients) reported the primary endpoint of pCR based on the predefined wait interval and were included in the qualitative and quantitative analysis for this outcome variable; 15·9 per cent (1522 of 9551) and 11·3 per cent (1481 of 13 099) had achieved pCR in the extended and classical intervals respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also found a number of treatment-related variables that are associated with a higher likelihood of complete response, including the interval from the end of radiation to surgery, 19,20,23,27,32,4042 type of concurrent chemotherapy used, 43 and radiation dose. 4446 In particular, the interval from the end of radiation to surgery has been of special interest and has been directly addressed by multiple studies as well as a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%